2021
DOI: 10.3390/cells10030568
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Evaluation of Isogenic iPSC as a Source of Cell Replacement Therapies in Patients with Kearns Sayre Syndrome

Abstract: Kearns Sayre syndrome (KSS) is mitochondrial multisystem disorder with no proven effective treatment. The underlying cause for multisystem involvement is the energy deficit resulting from the load of mutant mitochondrial DNA (mtDNA), which manifests as loss of cells and tissue dysfunction. Therefore, functional organ or cellular replacement provides a promising avenue as a therapeutic option. Patient-specific induced pluripotent stem cells (iPSC) have become a handy tool to create personalized cell -based ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The detailed procedure is described in previously published studies. [56,57] The hiPSCs were cultured in TeSR-E8 (0 5990, STEMCELL Technologies) on Geltrex (A1413302, Gibco) and allowed to differentiate toward fibroblast, cardiomyocytes (CMs) and NPCs using our previously published protocols. [55] Briefly, embryoid bodies (EBs) were prepared in suspension in low attachment plates (174 932, Thermo Scientific) and plated onto gelatin-coated plates on Day 8 (PMEF-CFL-P1, EMD Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed procedure is described in previously published studies. [56,57] The hiPSCs were cultured in TeSR-E8 (0 5990, STEMCELL Technologies) on Geltrex (A1413302, Gibco) and allowed to differentiate toward fibroblast, cardiomyocytes (CMs) and NPCs using our previously published protocols. [55] Briefly, embryoid bodies (EBs) were prepared in suspension in low attachment plates (174 932, Thermo Scientific) and plated onto gelatin-coated plates on Day 8 (PMEF-CFL-P1, EMD Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Human iPSCs carrying large‐scale mtDNA deletions have been generated from patients affected by KSS and PMPS (Cherry et al , 2013 ; Russell et al , 2018 ; Lester Sequiera et al , 2021 ; Peron et al , 2021 ; Hernández‐Ainsa et al , 2022 ). Initial studies showed defects in hematopoietic progenitors (Cherry et al , 2013 ), but the contribution of mtDNA deletions to the disease pathogenesis in differentiated progenies has not been addressed in detail.…”
Section: Ipscs and 3d Organoids As Next‐g...mentioning
confidence: 99%
“…During evolution, mitochondria forfeited most of their genes to the nuclear genome of eukaryotic cells [2,4], which drastically reduced the chromosomal mtDNA, whereas they acquired a myriad of new functions [2]. Contemporary human mtDNA is a circular molecule of 16 kilobases containing 37 genes encoding 13 subunits of Complexes I, III, IV, and V of the electron transport chain (ETC) as well as 22 tRNAs and 2 rRNAs that are necessary for mitochondrial translation machinery function [4,40] (Fig. 1).…”
Section: Homeostasis Of Mitochondrial Genomementioning
confidence: 99%
“…Nuclear reprogramming of peripheral blood mononuclear cells (PBMCs) purified from the blood of KSS patients into cardiomyocytes, neurons and fibroblasts generated ‘mutation‐free’ isogenic sources of cell replacement therapies [40]. Thus, promoting mtDNA segregation ‘drift’ towards wild‐type mtDNA or harnessing mitochondrial transplantation strategies [50] will be critical avenues for further therapeutic developments for KSS.…”
Section: Homeostasis Of Mitochondrial Genomementioning
confidence: 99%